2019
DOI: 10.1159/000502011
|View full text |Cite
|
Sign up to set email alerts
|

Salt and Water Retention Is Associated with Microinflammation and Endothelial Injury in Chronic Kidney Disease

Abstract: Multifrequency bioimpedance spectroscopy (BIS) is an established method for assessing fluid status in chronic kidney disease (CKD). However, the technique is lacking in predictive value and accuracy. BIS algorithms assume constant tissue resistivity, which may vary with changing tissue ionic sodium concentration (Na+). This may introduce significant inaccuracies to BIS outputs. To investigate this, we used 23 Na magnetic resonance imaging (MRI) to measure Na + in muscle and subcutaneous tissues of 10 healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 52 publications
2
21
0
Order By: Relevance
“…141 Furthermore, there are reports of specific biomarkers profiles, such as IL-8 and E-selectin (fluid overload) and intercellular adhesion molecules (salt distribution), that may play a significant and discriminatory role for a better understanding of fluid imbalance and other pathophysiological responses. 146 Some studies suggest salivary biomarkers, including metabolome, which could provide biochemical and genetic profiling of hydration status. The scope of new noninvasive metabolome profiles can be expanded to additional metabolites and key electrolytes whose concentrations in saliva, tear, and urine display close relationships with those in blood.…”
Section: Metabolomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…141 Furthermore, there are reports of specific biomarkers profiles, such as IL-8 and E-selectin (fluid overload) and intercellular adhesion molecules (salt distribution), that may play a significant and discriminatory role for a better understanding of fluid imbalance and other pathophysiological responses. 146 Some studies suggest salivary biomarkers, including metabolome, which could provide biochemical and genetic profiling of hydration status. The scope of new noninvasive metabolome profiles can be expanded to additional metabolites and key electrolytes whose concentrations in saliva, tear, and urine display close relationships with those in blood.…”
Section: Metabolomicsmentioning
confidence: 99%
“…Furthermore, there are reports of specific biomarkers profiles, such as IL‐8 and E‐selectin (fluid overload) and intercellular adhesion molecules (salt distribution), that may play a significant and discriminatory role for a better understanding of fluid imbalance and other pathophysiological responses 146 . Some studies suggest salivary biomarkers, including metabolome, which could provide biochemical and genetic profiling of hydration status.…”
Section: Dehydration Assessment Techniquesmentioning
confidence: 99%
“…In ESKD patients, E-selectin was reversely related to cardiovascular events, LVH, and total mortality, while a specified E-selectin gene polymorphism was associated with carotid atherosclerosis [127-129]. In a previous work, E-selectin and ICAM-1 were also correlated with salt and water retention in ESKD [130].…”
Section: Assessment Of Endothelial Dysfunction In Ckd: Biochemical Mamentioning
confidence: 99%
“…Furthermore, it was reported that hemodialysis in these patients resulted in a significantly lower muscle sodium content and a tendency to lower skin sodium compared with controls. In a study using 23 NaMRI to evaluate tissue sodium concentration in pre-dialysis CKD patients, it was reported that these patients had higher skin sodium concentrations, but no differences were found in sodium muscle concentrations [97]. Moreover, it was found that both salt and water accumulation in these patients was associated with the elevation of serum markers for endothelial activation and of inflammatory pathways.…”
Section: Extrarenal Tissue Sodium Storage In Ckdmentioning
confidence: 99%